The value of magnetic resonance angiography in evaluation of head and neck pathology: a pictorial essay - Kamarudin, Norie Azilah; Abdul Rahman, Zainun; Sa'at@Yusof, Azlin; Raja Lope Ahmad, Raja Ahmad Al'konee (2007)
Objectives; The aim of this presentation is to highlight the ability of Magnetic Resonance Angiography (MRA) in the clinical applications of head & neck pathology.